Preliminary Study of Subclinical Brain Alterations in Patients With Asymptomatic Carotid Vulnerable Plaques Using Intravoxel Incoherent Motion Imaging by Voxelwise Comparison: A Study of Whole-Brain Imaging Measures - Guo, Jiuqing; OuYang, Lirong; Wang, Xiaoyi; Liao, Weihua; Huang, Qing; He, Wei; Zhou, Gaofeng; Yang, Shuai (Frontiers in Neuroscience, 2020)
Objective: To preliminarily explore subclinical brain alterations in asymptomatic carotid vulnerable plaque group based on intravoxel incoherent motion imaging (IVIM) through voxelwise comparison in the whole brain. Materials and Methods: Forty-nine elderly participants underwent multi-b-value DWI, among who, twenty-four participants with asymptomatic carotid vulnerable plaques and < 50% stenosis were served as the test group, while the rest as the healthy control group. After fitting the double-exponential model, slow ADC (Ds) and the fraction of fast ADC (f) values of the whole brain were obtained, which then were compared in a voxelwise manner by two-sample t-test. Multiple comparisons were corrected by the family-wise error (FWE) method with a corrected threshold of P < 0.05. Pearson correlations between IVIM parameters in altered brain regions and blood pressure, glucose, lipid and homocysteine were calculated. Results: For the test group, the Z-normalized Ds values were significantly higher in the left median cingulate and paracingulate gyrus (DCG.L), posterior cingulate gyrus (PCG. L) and left precuneus gyrus (PCUN.L) (cluster size = 156) and in the left middle frontal gyrus (MFG.L), orbital middle frontal gyrus (ORBmid.L) and superior frontal gyrus (SFG.L) (cluster size = 165), the Z-normalized Ds values were significantly lower in the right middle temporal gyrus (MTG.R) and inferior temporal gyrus (ITG.R) (cluster size = 116), and the Z-normalized f-values were significantly lower in the MTG.R, ITG.R (cluster size = 85) (p ＜0.05, FWE correction). LDL-C was negatively correlated with the Z-normalized Ds values in the DCG.L, PCG.L, and PCUN.L (r = 0.601, p = 0.002). LDL-C was positively correlated with the Z-normalized f-value in the MTG.R and ITG.R (r = 0.405, p = 0.05). Systolic blood pressure was positively correlated with the Z-normalized Ds values in the MFG.L, ORBmid.L, and SFG.L (r = 0.433, p = 0.035). Conclusion: This study was the first to detect subclinical brain alterations in asymptomatic carotid vulnerable plaque group through IVIM using whole-brain voxelwise comparisons comparison, which were partially correlated with blood pressure and lipids. Thus, IVIM might be utilized as a noninvasive biomarker of microvascular and microstructural brain changes in asymptomatic carotid vulnerable plaque group.